Somatotype and body composition assessment of Iranian male elite athletes in combat sports - Shahram, F.; Hossein, K.; Farhad, M.S. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. I, 2008)
Introduction There is little normative data related to somatotype and body composition of Iranian elite athletes competing in high level international combat sport, including Wushu, Taekwondo, Wrestling, Judo, and Karate. However, data like these are essential for accurate profiling of athletes in their preparation for competition, or for use with talent development programs (Ackland T. R., 2006). With support of the I.R.Iran National Olympic Committee, the research team found an excellent opportunity to gather anthropometric data during October and November 2006 prior to the Doha Asian Games. Forty-five members of National teams (among them some of world and Asian champions) were examined on a battery of 17 anthropometric parameters of body composition, and somatotype according to International Society of the Advancement of Kinanthropometry (ISAK) protocol. The aim of this paper is to present a summary of the data in a form that may be readily utilized for athlete profiling purposes. Methods Iranian Men`s Wushu, Tae kwon do, Wrestling, Judo, and Karate national team athletes taking part in the Doha 2006 Asian Games were invited to participate in the study. All subjects (n=45) were landmarked by an ISAK-accredited level-3 anthropometrist with standardized parameters (Norton & Olds, 1996) and measured by level-1 accredited anthropometrists. Heath-Carter method and Whiters Equation were utilized for somatotyping and PBF estimation respectively. All statistical method was done by SPSS 13.